A Speech Act Analysis of Expressive Language in the Animated Movie Brave (2012): Investigating Emotional Communication Through Movie Dialogue - Eva Dwi Asri; Sigit Suharjono (Universitas Cokroaminoto Palopo, 2026)
This study examines the use of expressive speech acts in the movie ’’Brave’’ to identify their types and perlocutionary effects in character interactions. This research employs a descriptive qualitative method, focusing on the utterances produced by the characters in the film. Data were collected through observation and note-taking techniques and analyzed using Searle’s classification of expressive speech acts. The findings reveal that 36 locutions are categorized as expressive speech acts, which are classified into six types: thanking, congratulating, apologizing, complaining, welcoming, and praising. Among these types, complaining appears most frequently, while congratulating is the least frequent. Additionally, the interpretation of these speech acts is influenced by contextual factors and the responses of the interlocutors, which depend on the situation. Furthermore, the study finds that expressive speech acts produce various perlocutionary effects on the listeners, including happiness, silence, emotional reactions, disagreement, forgiveness, and supportive responses. These effects are reflected through both verbal and non-verbal reactions shown by the interlocutors during communication. Therefore, the findings highlight that expressive speech acts play an important role not only in conveying emotions and supporting character development but also in influencing the interlocutors’ attitudes and responses throughout the interactions in the movie.